Pediatric collaborative care outcomes in a regional model - Parkhurst, John T.; Garcia-Goetting, Catherine; Peist, Eric; Ballard, Rachel; Romba, Courtney; Lavigne, John V. (Frontiers in Psychiatry, 2023)
Background Despite the movement toward hospital-based medical centers acquiring pediatric primary care offices, many primary care pediatricians still work in small, independent practices. To expand mental healthcare access, service delivery models must consider primary care practice needs and regionally available resources. Objective This report describes the implementation and evaluation of the Mood, Anxiety, ADHD Collaborative Care (MAACC) program over a 4 years period. MAACC. MAACC engaged 97 pediatric primary care clinicians across 39 practices in mental health training and supported the treatment of referred patients through a collaborative care model. To support psychosocial treatment needs, we built a child community therapy referral network of 213 licensed psychotherapy providers. Methods Data were collected on service delivery patterns (e.g., referrals, treatment use, and attrition) and patient outcomes. Measures included parent and children and adolescents PROMIS anxiety and depression short forms and the Parent NICHQ Vanderbilt. Results Six hundred ninety-six children and adolescents aged 6–18 were evaluated and provided treatment recommendations. Anxiety disorders were the most common diagnosis (45.4%), followed by ADHD (30.7%) and mood disorder (17%). For children and adolescents with an anxiety or mood disorder, significant improvement was observed from baseline to any initial follow-up and from baseline to 6, 12-, and 18 weeks on children and adolescents and parent measures of anxiety and depression. For children and adolescents with ADHD, significant improvement was observed from baseline to any initial follow-up measure and at 6 and 18 weeks on parent-reported inattentive symptoms. Significant differences in treatment outcomes were identified for children and adolescents with anxiety receiving psychotherapy alone and medication management and psychotherapy. Conclusion MAACC utilization and patient outcomes suggest that real-world collaborative care can effectively provide high-quality care while cultivating increased primary care treatment capacity and building on existing community resources.